Bromodomain proteins regulate human cytomegalovirus latency and reactivation allowing epigenetic therapeutic intervention - Groves, Ian J. (Proc Natl Acad Sci U S A, 2021)
Reactivation of human cytomegalovirus (HCMV) from latency is a major health consideration for recipients of stem-cell and solid organ transplantations. With over 200,000 transplants taking place globally per annum, virus reactivation can occur in more than 50% of cases leading to loss of grafts as well as serious morbidity and even mortality. Here, we present the most extensive screening to date of epigenetic inhibitors on HCMV latently infected cells and find that histone deacetylase inhibitors (HDACis) and bromodomain inhibitors are broadly effective at inducing virus immediate early gene expression. However, while HDACis, such as myeloid-selective CHR-4487, lead to production of infectious virions, inhibitors of bromodomain (BRD) and extraterminal proteins (I-BETs), including GSK726, restrict full reactivation. Mechanistically, we show that BET proteins (BRDs) are pivotally connected to regulation of HCMV latency and reactivation. Through BRD4 interaction, the transcriptional activator complex P-TEFb (CDK9/CycT1) is sequestered by repressive complexes during HCMV latency. Consequently, I-BETs allow release of P-TEFb and subsequent recruitment to promoters via the superelongation complex (SEC), inducing transcription of HCMV lytic genes encoding immunogenic antigens from otherwise latently infected cells. Surprisingly, this occurs without inducing many viral immunoevasins and, importantly, while also restricting viral DNA replication and full HCMV reactivation. Therefore, this pattern of HCMV transcriptional dysregulation allows effective cytotoxic immune targeting and killing of latently infected cells, thus reducing the latent virus genome load. This approach could be safely used to pre-emptively purge the virus latent reservoir prior to transplantation, thereby reducing HCMV reactivation-related morbidity and mortality.